Real‐Time Dissection of the Transportation and miRNA‐Release Dynamics of Small Extracellular Vesicles (Adv. Sci. 7/2023). Issue 7 (3rd March 2023) - Xia, Hou‐Fu; Yu, Zi‐Li; Zhang, Li‐Juan; Liu, Shu‐Lin; Zhao, Yi; Huang, Jue; Fu, Dan‐Dan; Xie, Qi‐Hui; Liu, Hai‐Ming; Zhang, Zhi‐Ling; Zhao, Yi‐Fang; Wu, Min; et al.
Abstract : Single Particle Tracking of Extracellular Vesicles In article number 2205566, by developing a quantum dot‐assisted single particle tracking platform, Wei Zhang, Dai‐Wen Pang, Gang Chen, and co‐workers tracked the three‐stage transportation process of tumor‐derived small extracellular vesicles in endothelial cells, and further recorded their miRNA cargorelease details in real time. This dynamic process is similar to the coach‐mediated passenger transport monitored by satellite.